(untitled) (International Journal of Management and Sustainability, 2014)
Batik Semarang is one of Indonesia’s national heritage, which once had disappered in Japan colonialism era. In 2006, the city government of Semarang started to redevelop Batik Semarang as a regional identity of Semarang, by conducting a preservation program of Batik Semarang. This research’s objective is to identify and analyze the business performance of Batik craftsmen or batik maker in Semarang focused on the study on production, distribution, and market aspects. The fact arose is the decreasing number of Batik craftsmen year by year. The research was conducted by using the survey method on 17 batik craftsman in Semarang city. The Analysis of Batik Semarang’s Business Performance uses SCP approach which covers market structure analysis, conduct analysis, and performance analysis. The industry level market is moderately concentrated over the study indicated by the CR4 75% and HHI 1889. The result of market structure analysis suggest an oligopolistic market structure. Performance analysis involves the elements of price conduct, product conduct, and market conduct. Price conduct shows that 76 % of respondents act as the price maker. Product conduct shows that 70 % of respondents have chosen to do product diversification. Market conduct shows that 56 percent of producers sell the products directly to the consumers.. Performance analysis is viewed from the element of Batik business profitability, which shows the average R/C ratio of 1.72 and the average ROA of 0.51. This indicates that Batik Semarang business is still profitable.